High-strength pervious concrete and method for making same

CN122977784APending Publication Date: 2026-10-27XINTONGDA (SHENZHEN) CONSTRUCTION ENGINEERING CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611137230.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-07-29
Publication Date
2026-10-27

AI Technical Summary

Technical Problem

[0004]为了克服上述的技术问题,本发明的目的在于提供一种高强度透水混凝土及其制备方法,解决了现有的透水混凝土的力学强度偏低,难以满足重载交通或严苛环境下的使用要求的问题

Benefits of technology

本发明的一种高强度透水混凝土及其制备方法,通过将粗骨料、水泥、水、强度增强剂以及改性混杂纤维混合成型,之后浇筑、振实、养护成型,得到高强度透水混凝土;该制备方法通过向透水混凝土中添加强度增强剂,强度增强剂能够在透水混凝土内部形成交联结构,增强粗骨料与水泥浆体之间的粘结力,从而显著提升透水混凝土的力学性能,还向透水混凝土中添加改性混杂纤维,改性混杂纤维的桥接作用能够有效阻止混凝土在受力过程中微裂缝的扩展,从而提高其断裂韧性,进一步提升透水混凝土的力学性能,提升了透水混凝土的强度,从而提高了整体的承载能力和耐久性,增强了透水混凝土的整体耐久性能,提高了城市的排水能力,改善了城市排水系统的效能。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The application relates to the field of pervious concrete, in particular to high-strength pervious concrete and a preparation method thereof, and solves the problem that the mechanical strength of the existing pervious concrete is low and it is difficult to meet the use requirements under heavy-load traffic or severe environment; the preparation method adds a strength enhancer to the pervious concrete, the strength enhancer can form a cross-linking structure in the pervious concrete, enhances the adhesion between the coarse aggregate and the cement paste, and significantly improves the mechanical properties of the pervious concrete; modified hybrid fibers are also added to the pervious concrete, the bridging effect of the modified hybrid fibers can effectively prevent the expansion of micro-cracks in the concrete during the stress process, thereby improving the fracture toughness and further improving the mechanical properties of the pervious concrete, the strength of the pervious concrete is improved, the overall bearing capacity and durability are improved, the drainage capacity of the city is improved, and the efficiency of the urban drainage system is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of permeable concrete, and more specifically to a high-strength permeable concrete and its preparation method. Background Technology

[0002] With the acceleration of urbanization, permeable concrete, as an important eco-friendly paving material, is widely used in various urban infrastructure constructions due to its excellent permeability, such as urban roads, squares, and parking lots. Applying permeable concrete to these locations not only effectively solves drainage problems but also replenishes groundwater to a certain extent, improving the urban ecological environment. However, its inherent porous skeleton structure results in relatively low mechanical strength, making it difficult to meet the requirements of heavy traffic or harsh environments.

[0003] Therefore, developing a high-strength permeable concrete and its preparation method is of great practical significance. Summary of the Invention

[0004] In order to overcome the above-mentioned technical problems, the purpose of this invention is to provide a high-strength permeable concrete and its preparation method, which solves the problem that the existing permeable concrete has low mechanical strength and is difficult to meet the requirements of heavy traffic or harsh environments.

[0005] The objective of this invention can be achieved through the following technical solutions: In a first aspect, this application provides a high-strength permeable concrete, comprising the following components by weight: The composition includes 150-160 parts coarse aggregate, 20-25 parts cement, 6-8 parts water, 0.9-2.5 parts strength enhancer, and 0.2-1.4 parts modified hybrid fiber. The strength enhancing agent is prepared by the following steps: Step a1: Add pyrene and nitrobenzene to a three-necked flask equipped with a stirrer, thermometer, constant pressure dropping funnel and gas delivery tube. Purge with nitrogen for protection and stir the reaction at 20-25℃ and 200-300 r / min for 20-30 min. Then raise the temperature to 110-120℃ and continue stirring for 10-20 min. Then add bromine dropwise while stirring, controlling the dropping rate to 1-3 drops / s. After the addition is complete, continue stirring for 10-15 h. After the reaction is complete, cool the reaction product to room temperature and pour it into ethanol. Then filter under vacuum. Wash the filter cake 2-3 times with distilled water and then place it in a vacuum drying oven at 80-90℃ for 3-5 h to obtain polybrominated pyrene ring compounds. Step a2: Add the polybrominated pyrene compound, tris(hydroxymethyl)aminomethane, potassium carbonate, zinc powder, and N,N-dimethylformamide to a three-necked flask equipped with a stirrer, thermometer, and gas delivery tube. Purge with nitrogen for protection and stir the reaction at 20-25°C and 200-300 r / min for 20-30 min. Then raise the temperature to 110-120°C and continue stirring for 10-15 h. After the reaction is complete, cool the reaction product to room temperature, then filter under vacuum. Remove the solvent from the filtrate by rotary evaporation to obtain the polyhydroxy compound. Step a3: Add the polyhydroxy compound, hexamethylene diisocyanate, dibutyltin dilaurate, and toluene to a three-necked flask equipped with a stirrer, thermometer, and gas delivery tube. Purge with nitrogen for protection and stir the reaction at 20-25°C and 200-300 r / min for 10-20 min. Then raise the temperature to 50-60°C and continue stirring for 2-3 h. After that, raise the temperature to 90-100°C and continue stirring for 3-4 h. After the reaction is complete, cool the reaction product to room temperature and then remove the solvent by rotary evaporation to obtain the strength enhancer.

[0006] In a preferred embodiment of the present invention, the ratio of pyrene, nitrobenzene and bromine used in step a1 is 10 mmol: 100-110 mL: 23-25 ​​mmol.

[0007] In a preferred embodiment of the present invention, the ratio of the polybrominated pyrene compound, tris(hydroxymethyl)aminomethane, potassium carbonate, zinc powder and N,N-dimethylformamide in step a2 is 10 mmol: 40 mmol: 50-55 mmol: 0.01-0.02 g: 100-110 mL.

[0008] In a preferred embodiment of the present invention, the ratio of the polyhydroxy compound, hexamethylene diisocyanate, dibutyltin dilaurate, and toluene in step a3 is 10 mmol: 120 mmol: 0.08-0.12 g: 100-110 mL.

[0009] In a preferred embodiment of the present invention, the modified hybrid fiber is prepared by the following steps: Step b1: Add glass fiber, carbon fiber and acetone to a three-necked flask equipped with a stirrer, thermometer and gas delivery tube, and purge with nitrogen for protection. Stir and react for 20-30 min at a temperature of 20-25℃ and a stirring rate of 200-300 r / min. Then raise the temperature to 50-52℃ and continue stirring for 2-4 h. After the reaction is completed, cool the reaction product to room temperature, then filter under vacuum. Wash the filter cake 2-3 times with ethanol and distilled water, and then place it in a vacuum drying oven and dry it at a temperature of 80-90℃ for 2-3 h to obtain pretreated hybrid fibers. Step b2: Add ethanol and deionized water to a three-necked flask equipped with a stirrer, thermometer, and gas delivery tube. Purge with nitrogen for protection and stir for 2-3 minutes at 20-25℃ and 200-300 r / min. Then adjust the pH to 3-4 with oxalic acid, add silane coupling agent KH-550 and continue stirring for 2-4 hours. Then add pretreated hybrid fibers and continue stirring for 4-6 hours at 80-90℃. After the reaction is complete, cool the reaction product to room temperature, then vacuum filter. Wash the filter cake 2-3 times with distilled water and then place it in a vacuum drying oven and dry at 50-60℃ for 3-5 hours to obtain modified hybrid fibers.

[0010] In a preferred embodiment of the present invention, the ratio of glass fiber, carbon fiber and acetone used in step b1 is 5g:1-5g:80-90mL.

[0011] In a preferred embodiment of the present invention, the glass fiber in step b1 has a length of 12 mm, a diameter of 7 μm, and a density of 1.75 g / cm³. 3 The carbon fiber has a tensile strength of 4900 MPa and a tensile modulus of 230 GPa; the carbon fiber has a length of 12 mm, a diameter of 13 μm, and a density of 2.73 g / cm³. 3 The tensile strength is 1450 MPa and the tensile modulus is 75 GPa.

[0012] In a preferred embodiment of the present invention, the ratio of ethanol, deionized water, silane coupling agent KH-550 and pretreated mixed fibers in step b2 is 90-95mL:10-12mL:3-9g:5g.

[0013] Secondly, this application provides a method for preparing high-strength permeable concrete, comprising the following steps: Step 1: Weigh out 150-160 parts of coarse aggregate, 20-25 parts of cement, 6-8 parts of water, 0.9-2.5 parts of strength enhancer, and 0.2-1.4 parts of modified hybrid fiber according to the weight ratio, and set aside. Step 2: Mix coarse aggregate, cement, water, strength enhancer and modified hybrid fiber into a mold, then pour, vibrate and cure to obtain high-strength permeable concrete.

[0014] In a preferred embodiment of the present invention, the cement is P·O 42.5 grade ordinary Portland cement; the coarse aggregate is continuously graded crushed stone with a particle size of 5-20mm.

[0015] The beneficial effects of this invention are: This invention discloses a high-strength permeable concrete and its preparation method. The method involves mixing coarse aggregate, cement, water, a strength enhancer, and modified hybrid fibers, followed by pouring, compacting, and curing to obtain high-strength permeable concrete. The preparation method utilizes a strength enhancer to form a cross-linked structure within the permeable concrete, strengthening the bond between the coarse aggregate and the cement paste, thus significantly improving the mechanical properties of the permeable concrete. Furthermore, the addition of modified hybrid fibers effectively prevents the propagation of microcracks during stress, thereby improving its fracture toughness and further enhancing its mechanical properties and strength. This results in improved overall load-bearing capacity and durability, enhanced overall durability, improved urban drainage capacity, and improved efficiency of urban drainage systems.

[0016] In the preparation of high-strength permeable concrete, a strength enhancer is first prepared. This is achieved through a reaction between pyrene and bromine, where bromine acts as a brominating agent, introducing multiple bromine atoms onto the pyrene ring to obtain a polybrominated pyrene ring compound. Then, a reaction is performed between this polybrominated pyrene ring compound and tris(hydroxymethyl)aminomethane, where the bromine atoms on the polybrominated pyrene ring compound react with the amino groups on the tris(hydroxymethyl)aminomethane, introducing multiple hydroxyl groups to obtain a polyhydroxy compound. Finally, a reaction is performed between this polyhydroxy compound and hexamethylene diisocyanate, where the hydroxyl groups on the polyhydroxy compound react with the isocyanate groups on the hexamethylene diisocyanate, simultaneously introducing isocyanate groups to obtain the strength enhancer. The molecular structure of this strength enhancer contains a large number of isocyanate groups, which have high reactivity and can chemically react with the hydroxyl groups in cement hydration products, thereby forming a cross-linked structure within the permeable concrete. This cross-linked structure not only improves the density of the permeable concrete but also enhances the bond between aggregates and cement paste, significantly improving the compressive and flexural strength of the concrete, and ultimately enhancing its mechanical properties and durability.

[0017] In the process of preparing high-strength permeable concrete, a modified hybrid fiber was also prepared. Glass fibers and carbon fibers were treated with acetone to remove surface impurities, resulting in pretreated hybrid fibers. These pretreated hybrid fibers were then treated with a silane coupling agent, KH-550. The siloxanes on the KH-550 hydrolyzed to form silanols, which were then grafted onto the surface of the pretreated hybrid fibers. Simultaneously, amino groups were introduced, resulting in modified hybrid fibers. Carbon fibers possess high strength, which can improve concrete strength, while glass fibers have high ductility, which can enhance concrete toughness. The combination of these two fibers can improve the strength and toughness of permeable concrete, effectively preventing the propagation of microcracks during stress. Furthermore, after modification, the amino groups can chemically react with the isocyanate groups on the strength enhancer to form a strong chemical interface, further improving the mechanical properties and durability of the concrete. Detailed Implementation

[0018] The technical solutions of the present invention will be clearly and completely described below with reference to the embodiments of the present invention. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those of ordinary skill in the art without creative effort are within the scope of protection of the present invention.

[0019] Example 1: This embodiment describes a method for preparing high-strength permeable concrete, including the following steps: Step S1: 10 mmol of pyrene and 100 mL of nitrobenzene were added to a three-necked flask equipped with a stirrer, thermometer, constant pressure dropping funnel and gas delivery tube. Nitrogen gas was introduced for protection. The mixture was stirred at 20 °C and 200 r / min for 20 min. Then the temperature was raised to 110 °C and the mixture was stirred for another 10 min. Then 23 mmol of bromine was added dropwise while stirring, with the dropping rate controlled at 1 drop / s. After the addition was completed, the mixture was stirred for another 10 h. After the reaction was completed, the reaction product was cooled to room temperature and then poured into ethanol. The mixture was then vacuum filtered. The filter cake was washed twice with distilled water and then placed in a vacuum drying oven and dried at 80 °C for 3 h to obtain the polybrominated pyrene ring compound. Step S2: 10 mmol of polybrominated pyrene compound, 40 mmol of tris(hydroxymethyl)aminomethane, 50 mmol of potassium carbonate, 0.01 g of zinc powder and 100 mL of N,N-dimethylformamide were added to a three-necked flask equipped with a stirrer, thermometer and gas delivery tube. Nitrogen gas was introduced for protection. The mixture was stirred at 20 °C and 200 r / min for 20 min. Then the temperature was raised to 110 °C and the mixture was stirred for 10 h. After the reaction was completed, the reaction product was cooled to room temperature and then filtered under vacuum. The solvent was removed by rotary evaporation of the filtrate to obtain the polyhydroxy compound. Step S3: Add 10 mmol of polyhydroxy compound, 120 mmol of hexamethylene diisocyanate, 0.08 g of dibutyltin dilaurate and 100 mL of toluene to a three-necked flask equipped with a stirrer, thermometer and gas delivery tube. Purge with nitrogen for protection and stir at 20 °C and 200 r / min for 10 min. Then raise the temperature to 50 °C and continue stirring for 2 h. Then raise the temperature to 90 °C and continue stirring for 3 h. After the reaction is completed, cool the reaction product to room temperature and then remove the solvent by rotary evaporation to obtain the strength enhancer. Step S4: Add 5g of glass fiber, 1g of carbon fiber, and 80mL of acetone to a three-necked flask equipped with a stirrer, thermometer, and gas delivery tube. Purge with nitrogen for protection and stir at 20℃ and a stirring rate of 200r / min for 20min. Then, raise the temperature to 50℃ and continue stirring for 2h. After the reaction, cool the product to room temperature, then vacuum filter. Wash the filter cake twice with ethanol and distilled water, then place it in a vacuum drying oven and dry at 80℃ for 2h to obtain pretreated hybrid fibers. The glass fiber has a length of 12mm, a diameter of 7μm, and a density of 1.75g / cm³. 3 The carbon fiber has a tensile strength of 4900 MPa and a tensile modulus of 230 GPa; the carbon fiber has a length of 12 mm, a diameter of 13 μm, and a density of 2.73 g / cm³. 3 The tensile strength is 1450 MPa and the tensile modulus is 75 GPa; Step S5: Add 90 mL of ethanol and 10 mL of deionized water to a three-necked flask equipped with a stirrer, thermometer and gas delivery tube. Purge with nitrogen for protection and stir for 2 min at 20 °C and 200 r / min. Then adjust the pH to 3 with oxalic acid, add 3 g of silane coupling agent KH-550 and continue stirring for 2 h. Then add 5 g of pretreated hybrid fiber and continue stirring for 4 h at 80 °C. After the reaction is complete, cool the reaction product to room temperature, then vacuum filter. Wash the filter cake twice with distilled water and then place it in a vacuum drying oven and dry at 50 °C for 3 h to obtain modified hybrid fiber. Step S6: Weigh out 150 parts coarse aggregate, 20 parts cement, 6 parts water, 0.9 parts strength enhancer, and 0.2 parts modified hybrid fiber according to the following weight proportions, and set aside; the cement is P·O 42.5 grade ordinary Portland cement; the coarse aggregate is continuously graded crushed stone with a particle size of 5-20mm; Step S7: Mix coarse aggregate, cement, water, strength enhancer and modified hybrid fiber into a mold, then pour, vibrate and cure to obtain high-strength permeable concrete.

[0020] Example 2: This embodiment describes a method for preparing high-strength permeable concrete, including the following steps: Step S1: 10 mmol of pyrene and 105 mL of nitrobenzene were added to a three-necked flask equipped with a stirrer, thermometer, constant pressure dropping funnel and gas delivery tube. Nitrogen gas was introduced for protection. The mixture was stirred at 22 °C and 250 r / min for 25 min. Then the temperature was raised to 115 °C and the mixture was stirred for another 15 min. Then 24 mmol of bromine was added dropwise while stirring, with the dropping rate controlled at 2 drops / s. After the addition was completed, the mixture was stirred for another 12 h. After the reaction was completed, the reaction product was cooled to room temperature and then poured into ethanol. The mixture was then vacuum filtered. The filter cake was washed twice with distilled water and then placed in a vacuum drying oven and dried at 85 °C for 4 h to obtain the polybrominated pyrene ring compound. Step S2: 10 mmol of polybrominated pyrene compound, 40 mmol of tris(hydroxymethyl)aminomethane, 52 mmol of potassium carbonate, 0.015 g of zinc powder and 105 mL of N,N-dimethylformamide were added to a three-necked flask equipped with a stirrer, thermometer and gas delivery tube. Nitrogen gas was introduced for protection, and the mixture was stirred at 22 °C and 250 r / min for 25 min. Then the temperature was raised to 115 °C and the mixture was stirred for 12 h. After the reaction was completed, the reaction product was cooled to room temperature and then filtered under vacuum. The solvent was removed by rotary evaporation of the filtrate to obtain the polyhydroxy compound. Step S3: 10 mmol of polyhydroxy compound, 120 mmol of hexamethylene diisocyanate, 0.1 g of dibutyltin dilaurate and 105 mL of toluene were added to a three-necked flask equipped with a stirrer, thermometer and gas delivery tube. Nitrogen gas was introduced for protection. The mixture was stirred at 22 °C and 250 r / min for 15 min. Then the temperature was raised to 55 °C and the mixture was stirred for 2.5 h. After that, the temperature was raised to 95 °C and the mixture was stirred for 3.5 h. After the reaction was completed, the reaction product was cooled to room temperature and the solvent was removed by rotary evaporation to obtain the strength enhancer. Step S4: Add 5g of glass fiber, 3g of carbon fiber, and 85mL of acetone to a three-necked flask equipped with a stirrer, thermometer, and gas delivery tube. Purge with nitrogen for protection and stir at 22℃ and a stirring rate of 250r / min for 25min. Then, raise the temperature to 51℃ and continue stirring for 3h. After the reaction, cool the product to room temperature, then vacuum filter. Wash the filter cake twice with ethanol and distilled water, then place it in a vacuum drying oven and dry at 85℃ for 2.5h to obtain pretreated hybrid fibers. The glass fiber has a length of 12mm, a diameter of 7μm, and a density of 1.75g / cm³. 3 The carbon fiber has a tensile strength of 4900 MPa and a tensile modulus of 230 GPa; the carbon fiber has a length of 12 mm, a diameter of 13 μm, and a density of 2.73 g / cm³. 3 The tensile strength is 1450 MPa and the tensile modulus is 75 GPa; Step S5: Add 92 mL of ethanol and 11 mL of deionized water to a three-necked flask equipped with a stirrer, thermometer and gas delivery tube. Purge with nitrogen for protection and stir for 2.5 min at 22 °C and 250 r / min. Then adjust the pH to 3.5 with oxalic acid. Add 6 g of silane coupling agent KH-550 and continue stirring for 3 h. Add 5 g of pretreated hybrid fiber and continue stirring for 5 h at 85 °C. After the reaction is complete, cool the reaction product to room temperature and then filter under vacuum. Wash the filter cake twice with distilled water and then place it in a vacuum drying oven and dry at 55 °C for 4 h to obtain modified hybrid fiber. Step S6: Weigh out 155 parts coarse aggregate, 22 parts cement, 7 parts water, 1.7 parts strength enhancer, and 0.8 parts modified mixed fiber according to the following weight proportions, and set aside; the cement is P·O 42.5 grade ordinary Portland cement; the coarse aggregate is continuously graded crushed stone with a particle size of 5-20mm; Step S7: Mix coarse aggregate, cement, water, strength enhancer and modified hybrid fiber into a mold, then pour, vibrate and cure to obtain high-strength permeable concrete.

[0021] Example 3: This embodiment describes a method for preparing high-strength permeable concrete, including the following steps: Step S1: 10 mmol of pyrene and 110 mL of nitrobenzene were added to a three-necked flask equipped with a stirrer, thermometer, constant pressure dropping funnel and gas delivery tube. Nitrogen gas was introduced for protection. The mixture was stirred at 25 °C and 300 r / min for 30 min. Then the temperature was raised to 120 °C and the mixture was stirred for another 20 min. Then 25 mmol of bromine was added dropwise while stirring, with the dropping rate controlled at 3 drops / s. After the addition was completed, the mixture was stirred for another 15 h. After the reaction was completed, the reaction product was cooled to room temperature and then poured into ethanol. The mixture was then vacuum filtered. The filter cake was washed three times with distilled water and then placed in a vacuum drying oven and dried at 90 °C for 5 h to obtain the polybrominated pyrene ring compound. Step S2: 10 mmol of polybrominated pyrene compound, 40 mmol of tris(hydroxymethyl)aminomethane, 55 mmol of potassium carbonate, 0.02 g of zinc powder and 110 mL of N,N-dimethylformamide were added to a three-necked flask equipped with a stirrer, thermometer and gas delivery tube. Nitrogen gas was introduced for protection. The mixture was stirred at 25 °C and 300 r / min for 30 min. Then the temperature was raised to 120 °C and the mixture was stirred for 15 h. After the reaction was completed, the reaction product was cooled to room temperature and then filtered under vacuum. The solvent was removed by rotary evaporation of the filtrate to obtain the polyhydroxy compound. Step S3: 10 mmol of polyhydroxy compound, 120 mmol of hexamethylene diisocyanate, 0.12 g of dibutyltin dilaurate and 110 mL of toluene were added to a three-necked flask equipped with a stirrer, thermometer and gas delivery tube. Nitrogen gas was introduced for protection. The mixture was stirred at 25 °C and 300 r / min for 20 min. Then the temperature was raised to 50 °C and the mixture was stirred for 3 h. After that, the temperature was raised to 100 °C and the mixture was stirred for 4 h. After the reaction was completed, the reaction product was cooled to room temperature and the solvent was removed by rotary evaporation to obtain the strength enhancer. Step S4: Add 5g of glass fiber, 5g of carbon fiber, and 90mL of acetone to a three-necked flask equipped with a stirrer, thermometer, and gas delivery tube. Purge with nitrogen for protection and stir at 25℃ and a stirring rate of 300r / min for 30min. Then, raise the temperature to 52℃ and continue stirring for 4h. After the reaction, cool the product to room temperature, then vacuum filter. Wash the filter cake three times with ethanol and distilled water, then place it in a vacuum drying oven and dry at 90℃ for 3h to obtain pretreated hybrid fibers. The glass fiber has a length of 12mm, a diameter of 7μm, and a density of 1.75g / cm³. 3The carbon fiber has a tensile strength of 4900 MPa and a tensile modulus of 230 GPa; the carbon fiber has a length of 12 mm, a diameter of 13 μm, and a density of 2.73 g / cm³. 3 The tensile strength is 1450 MPa and the tensile modulus is 75 GPa; Step S5: Add 95 mL of ethanol and 12 mL of deionized water to a three-necked flask equipped with a stirrer, thermometer and gas delivery tube. Purge with nitrogen for protection and stir for 3 min at 25 °C and 300 r / min. Then adjust the pH to 4 with oxalic acid, add 9 g of silane coupling agent KH-550 and continue stirring for 4 h. Then add 5 g of pretreated hybrid fiber and continue stirring for 6 h at 90 °C. After the reaction is complete, cool the reaction product to room temperature, then vacuum filter. Wash the filter cake three times with distilled water and then place it in a vacuum drying oven and dry at 60 °C for 5 h to obtain modified hybrid fiber. Step S6: Weigh out 160 parts coarse aggregate, 25 parts cement, 8 parts water, 2.5 parts strength enhancer, and 1.4 parts modified hybrid fiber according to the following weight proportions, and set aside; the cement is P·O 42.5 grade ordinary Portland cement; the coarse aggregate is continuously graded crushed stone with a particle size of 5-20mm; Step S7: Mix coarse aggregate, cement, water, strength enhancer and modified hybrid fiber into a mold, then pour, vibrate and cure to obtain high-strength permeable concrete.

[0022] Comparative Example 1: This comparative example illustrates a method for preparing high-strength permeable concrete, comprising the following steps: Step S1: Weigh out 160 parts of coarse aggregate, 25 parts of cement, and 8 parts of water according to the weight ratio, and set aside; the cement is P·O 42.5 grade ordinary Portland cement; the coarse aggregate is continuously graded crushed stone with a particle size of 5-20mm; Step S2: Mix coarse aggregate, cement and water into a mold, then pour, vibrate and cure to obtain high-strength permeable concrete.

[0023] Comparative Example 2: This comparative example illustrates a method for preparing high-strength permeable concrete, comprising the following steps: Step S1: 10 mmol of pyrene and 110 mL of nitrobenzene were added to a three-necked flask equipped with a stirrer, thermometer, constant pressure dropping funnel and gas delivery tube. Nitrogen gas was introduced for protection. The mixture was stirred at 25 °C and 300 r / min for 30 min. Then the temperature was raised to 120 °C and the mixture was stirred for another 20 min. Then 25 mmol of bromine was added dropwise while stirring, with the dropping rate controlled at 3 drops / s. After the addition was completed, the mixture was stirred for another 15 h. After the reaction was completed, the reaction product was cooled to room temperature and then poured into ethanol. The mixture was then vacuum filtered. The filter cake was washed three times with distilled water and then placed in a vacuum drying oven and dried at 90 °C for 5 h to obtain the polybrominated pyrene ring compound. Step S2: 10 mmol of polybrominated pyrene compound, 40 mmol of tris(hydroxymethyl)aminomethane, 55 mmol of potassium carbonate, 0.02 g of zinc powder and 110 mL of N,N-dimethylformamide were added to a three-necked flask equipped with a stirrer, thermometer and gas delivery tube. Nitrogen gas was introduced for protection. The mixture was stirred at 25 °C and 300 r / min for 30 min. Then the temperature was raised to 120 °C and the mixture was stirred for 15 h. After the reaction was completed, the reaction product was cooled to room temperature and then filtered under vacuum. The solvent was removed by rotary evaporation of the filtrate to obtain the polyhydroxy compound. Step S3: 10 mmol of polyhydroxy compound, 120 mmol of hexamethylene diisocyanate, 0.12 g of dibutyltin dilaurate and 110 mL of toluene were added to a three-necked flask equipped with a stirrer, thermometer and gas delivery tube. Nitrogen gas was introduced for protection. The mixture was stirred at 25 °C and 300 r / min for 20 min. Then the temperature was raised to 50 °C and the mixture was stirred for 3 h. After that, the temperature was raised to 100 °C and the mixture was stirred for 4 h. After the reaction was completed, the reaction product was cooled to room temperature and the solvent was removed by rotary evaporation to obtain the strength enhancer. Step S4: Weigh out 160 parts coarse aggregate, 25 parts cement, 8 parts water and 2.5 parts strength enhancer according to the weight ratio, and set aside; the cement is P·O 42.5 grade ordinary Portland cement; the coarse aggregate is continuously graded crushed stone with a particle size of 5-20mm; Step S5: Mix coarse aggregate, cement, water and strength enhancer into a mold, then pour, vibrate and cure to obtain high-strength permeable concrete.

[0024] Comparative Example 3: This comparative example illustrates a method for preparing high-strength permeable concrete, comprising the following steps: Step S1: Add 5g of glass fiber, 5g of carbon fiber, and 90mL of acetone to a three-necked flask equipped with a stirrer, thermometer, and gas delivery tube. Purge with nitrogen for protection and stir at 25℃ and a stirring rate of 300r / min for 30min. Then, raise the temperature to 52℃ and continue stirring for 4h. After the reaction, cool the product to room temperature, then vacuum filter. Wash the filter cake three times with ethanol and distilled water, then place it in a vacuum drying oven and dry at 90℃ for 3h to obtain pretreated hybrid fibers. The glass fiber has a length of 12mm, a diameter of 7μm, and a density of 1.75g / cm³. 3 The carbon fiber has a tensile strength of 4900 MPa and a tensile modulus of 230 GPa; the carbon fiber has a length of 12 mm, a diameter of 13 μm, and a density of 2.73 g / cm³. 3 The tensile strength is 1450 MPa and the tensile modulus is 75 GPa; Step S2: Add 95 mL of ethanol and 12 mL of deionized water to a three-necked flask equipped with a stirrer, thermometer and gas delivery tube. Purge with nitrogen for protection and stir for 3 min at 25 °C and 300 r / min. Then adjust the pH to 4 with oxalic acid, add 9 g of silane coupling agent KH-550 and continue stirring for 4 h. Then add 5 g of pretreated hybrid fiber and continue stirring for 6 h at 90 °C. After the reaction is complete, cool the reaction product to room temperature and then filter under vacuum. Wash the filter cake three times with distilled water and then place it in a vacuum drying oven and dry at 60 °C for 5 h to obtain modified hybrid fiber. Step S3: Weigh out 160 parts by weight of coarse aggregate, 25 parts by weight of cement, 8 parts by weight of water and 1.4 parts by weight of modified mixed fiber, and set aside; the cement is P·O 42.5 grade ordinary Portland cement; the coarse aggregate is continuously graded crushed stone with a particle size of 5-20mm; Step S4: Mix coarse aggregate, cement, water and modified hybrid fibers, then pour, vibrate and cure to obtain high-strength permeable concrete.

[0025] The high-strength permeable concrete of Examples 1-3 and Comparative Examples 1-3 were subjected to performance tests according to GB / T 50081-2019. The test results are shown in the table below: Referring to the data in the table above, and based on the comparison between Examples 1-3 and Comparative Examples 1-3, it can be seen that the permeable concrete of this application has high compressive strength and flexural strength, indicating that the permeable concrete has high strength.

[0026] In the description of this specification, references to terms such as "an embodiment," "example," "specific example," etc., indicate that a specific feature, structure, material, or characteristic described in connection with that embodiment or example is included in at least one embodiment or example of the invention. In this specification, illustrative expressions of the above terms do not necessarily refer to the same embodiment or example. Furthermore, the specific features, structures, materials, or characteristics described may be combined in any suitable manner in one or more embodiments or examples.

[0027] The above description is merely an example and illustration of the present invention. Those skilled in the art can make various modifications or additions to the specific embodiments described or use similar methods to replace them, as long as they do not deviate from the invention or exceed the scope defined in this application, they should all fall within the protection scope of the present invention.

Claims

1. A high-strength permeable concrete, characterized in that, Includes the following components by weight: The composition includes 150-160 parts coarse aggregate, 20-25 parts cement, 6-8 parts water, 0.9-2.5 parts strength enhancer, and 0.2-1.4 parts modified hybrid fiber. The strength enhancing agent is prepared by the following steps: Step a1: Pyrene and nitrobenzene were stirred and reacted, then bromine was added dropwise and the reaction was continued with stirring. After the reaction was completed, the reaction product was cooled and then poured into ethanol. After vacuum filtration, the filter cake was washed and dried to obtain polybrominated pyrene ring compounds. Step a2: The polybrominated pyrene compound, tris(hydroxymethyl)aminomethane, potassium carbonate, zinc powder and N,N-dimethylformamide were stirred and reacted. After the reaction was completed, the reaction product was cooled, then vacuum filtered, and the filtrate was evaporated by rotary evaporation to obtain the polyhydroxy compound. Step a3: The polyhydroxy compound, hexamethylene diisocyanate, dibutyltin dilaurate and toluene are stirred and reacted. After the reaction is completed, the reaction product is cooled and then rotary evaporated to obtain the strength enhancer.

2. The high-strength permeable concrete according to claim 1, characterized in that, The ratio of pyrene, nitrobenzene and bromine used in step a1 is 10 mmol: 100-110 mL: 23-25 ​​mmol.

3. The high-strength permeable concrete according to claim 1, characterized in that, The ratio of the polybrominated pyrene compound, tris(hydroxymethyl)aminomethane, potassium carbonate, zinc powder, and N,N-dimethylformamide used in step a2 is 10 mmol: 40 mmol: 50-55 mmol: 0.01-0.02 g: 100-110 mL.

4. The high-strength permeable concrete according to claim 1, characterized in that, The ratio of the polyhydroxy compound, hexamethylene diisocyanate, dibutyltin dilaurate, and toluene in step a3 is 10 mmol: 120 mmol: 0.08-0.12 g: 100-110 mL.

5. The high-strength permeable concrete according to claim 1, characterized in that, The modified hybrid fiber is prepared by the following steps: Step b1: Glass fiber, carbon fiber and acetone are stirred and reacted. After the reaction is completed, the reaction product is cooled and then vacuum filtered. The filter cake is washed and dried to obtain pretreated hybrid fibers. Step b2: Ethanol and deionized water are stirred and reacted. Then, the pH is adjusted with oxalic acid. Then, silane coupling agent KH-550 and pretreated hybrid fibers are added and the reaction is continued with stirring. After the reaction is completed, the reaction product is cooled and then vacuum filtered. The filter cake is washed and dried to obtain modified hybrid fibers.

6. The high-strength permeable concrete according to claim 5, characterized in that, The ratio of glass fiber, carbon fiber and acetone used in step b1 is 5g:1-5g:80-90mL.

7. The high-strength permeable concrete according to claim 5, characterized in that, In step b2, the ratio of ethanol, deionized water, silane coupling agent KH-550, and pretreated mixed fibers is 90-95 mL: 10-12 mL: 3-9 g: 5 g.

8. A method for preparing high-strength permeable concrete as described in any one of claims 1-7, characterized in that, Includes the following steps: Step 1: Weigh out 150-160 parts of coarse aggregate, 20-25 parts of cement, 6-8 parts of water, 0.9-2.5 parts of strength enhancer, and 0.2-1.4 parts of modified hybrid fiber according to the weight ratio, and set aside. Step 2: Mix coarse aggregate, cement, water, strength enhancer and modified hybrid fiber into a mold, then pour, vibrate and cure to obtain high-strength permeable concrete.

9. The method for preparing high-strength permeable concrete according to claim 8, characterized in that, The cement is P·O 42.5 grade ordinary Portland cement; the coarse aggregate is continuously graded crushed stone with a particle size of 5-20mm.